Fiber Optic Sensors For Infrastructure Health Monitoring. - Noori, Mohammad (Momentum Press, 2018)
Structural health monitoring (SHM) can be characterized as the integration of sensing and intelligence to enable the potential damage to be monitored, analyzed, localized, and predicted in real time and in a nondestructive manner. Over the past two decades, extensive research has demonstrated that fiber-optic sensors (FOSs) are well suited for SHM sensing requirements in infrastructure systems. In this book, a brief overview of SHM and the application of FOS are presented. The book focuses on advanced techniques that utilize fiber-optic long-gauge sensing and overcome the limitations of traditional sensing and fulfill the requirements of infrastructure systems. The long-gauge FOSs have the merit of revealing both micro- and macrolevel information. Subsequently, a new approach, areawise distributed monitoring, is thoroughly discussed and its superior performance in SHM demonstrated. Finally, the application of areawise distributed monitoring, combined with the aforementioned long-gauge sensing technique, is presented for groups and networks of complex infrastructure systems.